ANALYSIS OF PAYANG FISHERMEN’S INCOME AT THE NUSANTARA FISHERIES PORT (PPN) PALABUHANRATU - Hamdan, Muhamad Ari; Maulina, Ine; Iskandar, Iskandar; Gumilar, Iwang (Universitas Mataram, 2025)
This study aims to analyze business income, profit-sharing systems, and the income of payang fishermen at the Nusantara Fisheries Port (PPN) Palabuhanratu, Sukabumi Regency. The research employs a quantitative descriptive method involving 17 payang fishing boats as samples chosen through random sampling. Primary data were collected via structured interviews, while secondary data came from official documents of PPN Palabuhanratu. The results reveal that the average net income per trip during the off-season, moderate, and peak seasons were IDR 3,500,440, IDR 4,310,359, and IDR 4,130,308, respectively. The profit-sharing system applied is a 2:1 distribution, with two parts for the boat owner and one part for the fishermen, plus an additional 5% for the helmsman. The boat owners earn between IDR 28–61 million per month, helmsmen earn IDR 3.5–7.7 million, and crew members earn IDR 1.2–2.7 million monthly. Compared to the 2024 Sukabumi minimum wage of IDR 3,351,883, only helmsmen during the moderate and peak seasons earn above the standard, while the crew members remain below the minimum wage across all seasons. Factors affecting fishermen’s income include season conditions, number of trips, catch volume, fish prices, and profit-sharing patterns. These findings indicate that the income of payang fishermen remains seasonal and unstable, especially for crew members, necessitating policy efforts to improve their welfare.